Intraoperative diagnosis of Bouveret syndrome requiring urgent endoscopic intervention: A case report - Zehara Abidi; Shrey Dalwadi; Avneet Singh; Robert Kim; Alexander Garcia; Ishita Dhawan; Adam Elfant (SAGE Open Medical Case Reports, 2025)
Bouveret syndrome is a rare complication of gallstone ileus with a high mortality rate. It is defined as the migration of a large gallstone through a cholecystoduodenal fistula leading to gastric outlet obstruction. During this case, gastroenterology was urgently paged to the operating room during an elective cholecystectomy in a 61-year-old female when a large gallstone was found in a fistula. Subsequently, mechanical lithotripsy and basket removal of the stone were performed. This case highlights the importance of swift diagnosis and utility of less-invasive endoscopy procedures for treatment of Bouveret syndrome.